Green Infrastructure Network Planning in Urban Fringe Areas Based on the Characteristics of Agricultural and Forestry Landscape Ecological Network in a Metropolitan City - Dongmeng Wang; Can Zhao; Baolin Xia; Chenming Zhang; Dezheng Kong; Qindong Fan (Land)
Small-scale, dispersed agroforestry spaces in the urban fringe constitute ecological land that serves dual public benefit functions: natural ecological conservation and rural-urban services. The purpose of this study is to construct a green infrastructure network by integrating the existing and potential green spaces in an urban fringe. The urban fringe in Zhengzhou was chosen as the study site. First, the urban fringe of Zhengzhou was identified based on multi-source data and artificial intelligence, followed by the extraction of green infrastructure elements through morphological spatial pattern analysis. Then, a public benefit output evaluation system was constructed to assess the land value of green infrastructure in the study area. Finally, based on the evaluation results, a classified network planning was conducted, and a triple-network integrated planning strategy was proposed. The results showed that (1) the administrative area of Zhengzhou is divided into three spatial types: urban core areas, the urban fringe areas, and urban periphery area; this study focuses on the urban fringe surrounding the main urban area of Zhengzhou, area of 678.93 km2; (2) the patch sizes of green infrastructure land in the study area range from approximately 0.01 km2 to 2.83 km2; (3) green infrastructure land was classified into levels 1~5 based on ecological conservation and rural-urban services, and comprehensive high-grade land was identified for the construction of the green infrastructure network; and (4) the green infrastructure network in the study area was divided into the forest natural habitat network, the blue-green infrastructure network, and the agroforestry landscape recreation network, and a triple-network integrated green infrastructure network strategy was developed. This study aims to strengthen the effective protection and utilization of micro-habitats in the urban fringe, contributing to the formulation of strategies to reduce the ecological vulnerability of the urban fringe and promote sustainable urban development.